2023
DOI: 10.1002/adfm.202308405
|View full text |Cite
|
Sign up to set email alerts
|

Zincophilic Anionic Hydrogel Electrolyte with Interfacial Specific Adsorption of Solvation Structures for Durable Zinc Ion Hybrid Supercapacitors

Gaozhi Guo,
Chenchen Ji,
Hongyu Mi
et al.

Abstract: The rechargeable zinc ion hybrid supercapacitors (ZHSCs) are critically hindered by the low Coulombic efficiency and poor lifespan due to the continuous water‐induced side reactions and uncontrolled dendrite growth of the Zn anode. Herein, a zincophilic anionic hydrogel electrolyte (PSCA/Zn(OTf)2) is constructed by incorporating the dodecyl sulfate anions ((OSO3R)−) micelles to manipulate the solvation structures of Zn2+ cations via the moderate ion–ion coordination interactions for manipulating the Zn deposit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(5 citation statements)
references
References 76 publications
0
5
0
Order By: Relevance
“…Natural balsa wood was chosen as substrate because of its lightweight, well-aligned channels and gradient-porosity. 26,27 After delignification, DW had higher charge density, better electrochemical stability, as well as higher hydrophilicity and specific surface area (Fig. S1, S2 and Table S2†), which improved the bonding force and electrochemical performance of the electrolyte.…”
Section: Resultsmentioning
confidence: 99%
“…Natural balsa wood was chosen as substrate because of its lightweight, well-aligned channels and gradient-porosity. 26,27 After delignification, DW had higher charge density, better electrochemical stability, as well as higher hydrophilicity and specific surface area (Fig. S1, S2 and Table S2†), which improved the bonding force and electrochemical performance of the electrolyte.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, some of the SMA can be assembled into OP-10 through hydrophobic interactions and become encapsulated within the micelles. Consequently, after the free radical polymerization, the PSMA segments formed and penetrated through the OP-10 micelle. , Then, the thermal- and pH- responsive monomer DMAEMA (for volume change), hydrophilic monomer AM, and pH-responsive monomer VPES (for visible color variation) were added to the DPM solution along with the initiator and cross-linking agent (PEGDA) followed by thermal polymerization under room temperature for 1 h to prepare the PADS@DPM hydrogel as the first layer. Subsequently, a reactant solution containing NIPAM, DMAEMA, the initiator, and the cross-linking agent was injected into the mold to form the second PND layer.…”
Section: Resultsmentioning
confidence: 99%
“…To address this, regulating the solvation structure and thereby the ion transport behavior by structuring/functionalizing the polymer matrix is attracting soaring interest in the GPE research community. 205,206 Chen's group suggested that the interaction between DMF-dehydrofluorinated PVDF and the [DMF–Li + ] complex promotes the charge carrier along PVDF segmental chains (Fig. 9(a1)).…”
Section: Design and Engineering Strategies Of Gpes For Wide-temperatu...mentioning
confidence: 99%
“…11(b 1 )). 84,206,229,241 For example, Luo and co-workers developed a GPE composed of 0.5 M NaPF 6 /diglyme in polymerized 1,3-dioxolane (poly-DOL). They indicated that the poly-DOL segments in the GPE help to weaken the interaction between Na + ions and diglyme solvents and confine the PF 6 − anions.…”
Section: Design and Engineering Strategies Of Gpes For Wide-temperatu...mentioning
confidence: 99%